2019
DOI: 10.1108/ijbm-10-2018-0281
|View full text |Cite
|
Sign up to set email alerts
|

The antecedents and consequences of financial literacy: a meta-analysis

Abstract: Purpose The purpose of this paper is to determine the antecedents and consequences of financial literacy by using meta-analytic techniques. Design/methodology/approach The authors conducted a meta-analysis of 44 valid studies, which generated a total of 690 observations (effect sizes). Findings The findings showed that the factors influencing financial literacy were as follows: educational level, financial attitude, financial knowledge, financial behaviour, gender, household income and investments. The con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 61 publications
1
48
1
9
Order By: Relevance
“…Some empirical papers examine the demographic, socio‐economic, personal, structural and cultural factors affecting financial literacy. Major factors determining financial literacy are gender, education, income, household investments, financial knowledge, financial attitude and financial behaviour (Santini et al., 2019). Regional differences in the environment one lives in impact financial literacy index, along with demographic and socio‐economic factors (Cucinelli, Trivellato, & Zenga, 2019).…”
Section: Mapping the Trends In Financial Literacy Research In The Lasmentioning
confidence: 99%
See 1 more Smart Citation
“…Some empirical papers examine the demographic, socio‐economic, personal, structural and cultural factors affecting financial literacy. Major factors determining financial literacy are gender, education, income, household investments, financial knowledge, financial attitude and financial behaviour (Santini et al., 2019). Regional differences in the environment one lives in impact financial literacy index, along with demographic and socio‐economic factors (Cucinelli, Trivellato, & Zenga, 2019).…”
Section: Mapping the Trends In Financial Literacy Research In The Lasmentioning
confidence: 99%
“…This definition was further expanded to financial capability according to which a financially capable person has an understanding of credit, debt, budget, insurance and all other financial dimensions. Positive financial behaviour is found to be a culmination of financial literacy (Santini, Ladeira, Mette, & Ponchio, 2019) and such behaviour is also influenced by a number of unexplored factors (Riitsalu & Põder, 2016). The lifecycle model developed by Lusardi and Mitchell (2014) suggests that people who receive financial education perform better than those who don't.…”
Section: Introductionmentioning
confidence: 99%
“…A recent focus is turning attention towards financial capability measurement. There is scope to expand related studies to compare and establish the rationale behind financial capability advent (Kempson et al, 2013;Luukkanen & Uusitalo, 2019;Santini et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A report from OECD (2013) defines financial literacy as a mixture of skill, behaviour, awareness, attitude, and knowledge, which are essential for sound financial decisions making for an individual to achieve the state of financial well-being. Many scholars and experts stated that financial literacy is inclusive of the three components: financial attitude, financial knowledge, and financial behaviour (Atkinson & Messy, 2012;Garg & Singh, 2018;Huston, 2010;Potrich et al, 2015;Santini et al, 2019). Thus, the above expositions expressed that financial literacy covered three broad concepts: financial attitude, financial knowledge, and financial behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Psychological elements such as attitudes, skills, motivations and personality traits may explain differences in the financial wellbeing of individuals in similar sociodemographic environments and moments of life (Brüggen et al, 2017). The reviewed studies show that, regardless of the concept or measurement tool used, women's financial knowledge has been shown to be equal to or lower than, but not greater than, that of men (Al-Bahrani et al, 2020;Chambers et al, 2019;Gerrans et al, 2014;Karakurum-Ozdemir et al, 2019;Kirbiš et al, 2017;Santini et al, 2019). For example, Karakurum-Ozdemir et al (2019) found that women have lower levels of financial knowledge in four of the five developing countries studied and the gender gap was not affected by educational differences between men and women but was reduced when income was controlled.…”
Section: Psychologicalmentioning
confidence: 99%